The Role of Mentors in Instilling Religious Values in Children - Aprillia Mahtuah Kotin; Heni Nopianti; Diyas Widiyarti (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The orphanage supervisor plays an important role in instilling religious values ​​in the orphanage children, especially in building the religious foundation for those from low-income backgrounds who lack parents to guide them directly. This study aims to determine and explain the role of the supervisor in instilling religious values ​​in children at the Guyub Rukun Orphanage. This study employs a descriptive qualitative approach, specifically a case study type,  utilizing a purposive sampling technique to cover 4 informants: 2 orphanage supervisors who serve as the head of the orphanage, and 2 orphanage children. This study uses Talcott Parsons Structural Functionalism theory to collect data using non-participant observation, in-depth interviews, and documentation. Data analysis refers to the interactive model of Miles and Huberman, which consists of three stages: data reduction, data presentation, and drawing conclusions and verification. The results of this study show that instilling religious values ​​is achieved by building habits of religious practice, such as congregational prayer and religious studies, and by fostering an attitude of mutual respect and discipline. Instilling religious values ​​emphasizes the importance of mentors as role models ​​for orphanage children facing difficult economic conditions and lacking religious guidance from their families. This shows that mentors have a role as educators, spiritual guides, moral role models, and substitute parents in shaping the religious values ​​of orphanage children. There are challenges caused by foster children not living permanently in the orphanage.